Generation of ten human induced pluripotent stem cell lines (hiPSCs) from patients with and without Chemotherapy-Induced Peripheral Neuropathy (CIPN) and Post Chemotherapy Cognitive Impairment (PCCI) - Karyn Lewis; Valeria Fernandez Vallone; Adam Dordevic; Johannes Kern; Harald Stachelscheid; Matthias Endres; Wolfgang Boehmerle; Petra Huehnchen; Christian Schinke (Stem Cell Research)
Chemotherapy-induced peripheral neuropathy (CIPN) and post-chemotherapy cognitive impairment (PCCI) represent major side effects of chemotherapy. Using Sendai virus vectors, ten hiPSC lines from patients who had undergone chemotherapy and did or did not develop CIPN and PCCI were generated. Each line was characterized to confirm markers of the undifferentiated state, differentiation potential, genomic integrity, identity verification and reprogramming vector removal. These lines serve as a valuable resource to create two disease models for 1) CIPN (hiPSC lines from five patients with CIPN vs. five without CIPN) and 2) PCCI (hiPSC lines from four patients with PCCI vs. five without PCCI).